TEKNOLOGI AKSARA LONTARA DI ERA INFORMASI TEKNOLOGI 4.0 - Yusring Sanusi Baso (Hasanuddin University, 2019)
The aim of this paper is to show the development of number and marking of Lontara’s script. The development is to provide and make a specific and additional marking character of Lontara. Those characters developed furthermore in the form of electronically program that able to be run at word office, both under windows and opensource (linux). The program used in making of Lontara’s number and its additional marking character is Fontmonger program. The obtained result of this development is a file program that available to be run properly either at word office or opensource and the file is called ltrunhas.ttf.